Radial Data Mining to Identify Density–Dose Interactions That Predict Distant Failure Following SABR - Davey, Angela; van Herk, Marcel; Faivre-Finn, Corinne; McWilliam, Alan (Frontiers in Oncology, 2022)
Purpose: Lower dose outside the planned treatment area in lung stereotactic radiotherapy has been linked to increased risk of distant metastasis (DM) possibly due to underdosage of microscopic disease (MDE). Independently, tumour density on pre-treatment computed tomography (CT) has been linked to risk of MDE. No studies have investigated the interaction between imaging biomarkers and incidental dose. The interaction would showcase whether the impact of dose on outcome is dependent on imaging, hence, if imaging could inform which patients require dose-escalation outside the gross tumour volume (GTV). We propose an image-based data mining methodology to investigate density-dose interactions radially from the GTV to predict DM with no a priori assumption on location. Methods: Dose and density were quantified in 1mm annuli around the GTV for 199 patients with early-stage lung cancer treated with 60Gy in 5 fractions. Each annulus was summarised by three density and three dose parameters. For parameter combinations, Cox regressions were performed including a dose-density interaction in independent annuli. Heat-maps were created that described improvement in DM prediction due to the interaction. Regions of significant improvement were identified and studied in overall outcome models. Results: Dose-density interactions were identified that significantly improved prediction for over 50% of bootstrap resamples. Dose and density parameters were not significant when the interaction was omitted. Tumour density variance and high peritumour density were associated with DM for patients with more cold spots (less than 30Gy EQD2) and non-uniform dose about 3cm outside of the GTV. Associations identified were independent of mean GTV dose. Conclusions: Patients with high tumour variance and peritumour density have increased risk of DM if there is low and non-uniform dose outside the GTV. The dose regions are independent of tumour dose, suggesting incidental dose may play an important role in controlling occult disease. Understanding such interactions is key to identifying patients who will benefit from dose-escalation. The methodology presented allowed spatial dose-density interactions to be studied at the exploratory stage for the first time. This could accelerate clinical implementation of imaging biomarkers by demonstrating the impact of incidental dose for tumours of varying characteristics in routine data.